Learning capacities and welfare in an Antillean manatee, Trichechus manatus manatus - Hénaut, Yann; Lara-Sánchez, Lizbeth Esmeralda; Morales-Vela, Benjamín; Machkour-M’Rabet, Salima (Comptes Rendus Biologies, 2020)
Studies on the cognitive abilities of manatees are limited despite their importance for the environmental enrichment and welfare of individuals in captivity and the understanding of manatee behaviour in the wild. Our study analyses how the presence of new stimuli and their association with food may have changed the behaviour of an Antillean manatee called Daniel. First, Daniel was observed in the absence of stimuli and subsequently, in step two, presented with the presence of four different geometrical shapes. During step three, we trained Daniel to eat from the square, while in step four he was presented with the four shapes without food. The behaviour and interaction of the manatee with the square increased considerably. We observed that three and twelve months after training the manatee still chose the square and displayed behaviours toward this specific shape. This study allowed us to formally demonstrate the ability of manatees to associate visual cues with food and increase activity with environmental and occupational devices. Our results open up new perspectives for behavioural studies on manatees, in particular those associated with cognition, management and welfare in captivity.